Dynamic Capabilities and Innovation Implications for Business Sustainability - Suharto Suharto; Siti Handayani Maulidina; Muhammad Harri; Titi Kurnia Fitriati; Iwan Kurniawan Subagja (Management Analysis Journal, 2023)
The aims of this study are to: 1) test and analyze the effect of dynamic capabilities on innovation 2) test and analyze the effect of capabilities on business continuity 3) test and analyze the effect of innovation on business continuity 4) test and analyze the effect of dynamic capabilities and innovation on business continuity. The research was conducted on Micro, Small and Medium Enterprises in Indonesia with a sample of 93 respondents. This research is quantitative of research by distributing questionnaires to Micro, Small and Medium Enterprises entrepreneurs. The sampling technique uses the saturation technique. Methods of data analysis using descriptive analysis and path analysis. The results of the study show that: 1) dynamic capabilities have a positive and significant effect on innovation 2) dynamic capabilities have a positive and significant effect on business continuity 3) dynamic capabilities have a positive and significant effect on business continuity 4) dynamic capabilities and innovation have a significant positive effect on continuity business.